The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00436-007-0575-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of avian malaria (Protozoa) in the endangered lesser kestrel, Falco naumanni

Abstract: We genetically analyzed avian malaria (Protozoa) isolated from lesser kestrels (Falco naumanni) breeding in La Mancha, Central Spain. A total of 586 adult individuals were screened for blood parasites using a very efficient polymerase chain reaction approach that amplifies a partial segment (498 bp) of the cytochrome b gene of avian malaria of the genera Haemoproteus and Plasmodium. The prevalence of Plasmodium was 8.2%, and the prevalence of Haemoproteus was 4.1%. Sequence analyses revealed six unique lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 11 publications
(17 reference statements)
0
45
0
Order By: Relevance
“…It contrasts, for example, with six avian malaria lineages (n=586 individuals screened) found in the lesser kestrel and 26 (n=415) observed in the blackcap Sylvia atricapilla (Ortego et al 2007;Pérez-Tris et al 2007). The Canary Islands are close to African mainland sources of host and parasite populations and receive a lot of migrants such as the blackcap every year that could elevate parasite richness.…”
Section: Genetic Characterizationmentioning
confidence: 91%
See 2 more Smart Citations
“…It contrasts, for example, with six avian malaria lineages (n=586 individuals screened) found in the lesser kestrel and 26 (n=415) observed in the blackcap Sylvia atricapilla (Ortego et al 2007;Pérez-Tris et al 2007). The Canary Islands are close to African mainland sources of host and parasite populations and receive a lot of migrants such as the blackcap every year that could elevate parasite richness.…”
Section: Genetic Characterizationmentioning
confidence: 91%
“…found in Berthelot's pipit (Fig. 4) have also been identified in lesser kestrels (Falco naumannii, Ortego et al 2007). Recent molecular studies have demonstrated that avian blood parasites of the genera Haemoproteus and Plasmodium show a lower degree of host specific than was previously thought (Bench et al 2000;Waldenström et al 2002;Szymanski and Lovette 2005), although it is lower in Plasmodium than in Haemoproteus parasites (Beadell et al 2004;Fallon et al 2005).…”
Section: Genetic Characterizationmentioning
confidence: 95%
See 1 more Smart Citation
“…This study describes the first molecular detection along with the microscopic examination of a Haemoproteus infection in a Tawny Owl (Strix aluco) in Turkey. As the ability of microscopic examinations to detect haemosporidian infections was very low compared with molecular approaches (9,17,21,24), the status of avian haemosporidiosis needs to be updated in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies analyzing data obtained on the basis of visual examination of blood smears are likely to have disregarded and/or confounded different and potentially pathological effects of cryptic lineages. Furthermore, recent studies have shown that several malaria lineages are undetected by traditional visual blood smear analyses, indicating that the prevalence of malaria has been severely underestimated (Waldenström et al 2004;Ortego et al 2007a). However, although molecular techniques have now been widely applied to the study of avian malaria parasites, to the best of our knowledge only a single study has analyzed the consequences on host fitness of different molecularly typed lineages in a wild bird population (Bensch et al 2007).…”
Section: Introductionmentioning
confidence: 98%